Construction of MoO2@MoS2 heterostructures in situ on carbon cloth for the hydrogen evolution reaction. (12th October 2021) - Tian, Jingyang; Yang, Chundi; Liu, Zhirui; Li, Funan; He, Xiao; Chen, Wei; Xia, Nan Nan; Lin, Chong
Abstract : MoO2 @MoS2 heterostructures in situ grown on carbon cloth were developed for efficient hydrogen evolution reaction. Abstract : MoS2 as one graphene-like 2D layered transition metal sulfide has attracted great attention. However, its application for the HER is still restricted by the poor electrical conductivity and structural restacking. In this work, we developed a facile method to prepare MoO2 @MoS2 heterostructures in situ by partial conversion of MoO x into MoS2 on carbon cloth. Based on the two-time hydrothermal process, the MoS2 nanosheets can be dispersed and grow on carbon cloth. Excellent electrochemical HER activity of MoO2 @MoS2 /CC-2 can be achieved with a low overpotential of 115 mV at 10 mA cm −2 ( η 10 ) in 0.5 M H2 SO4 . Furthermore, it still shows durable electrocatalytic stability for 13 h. The outstanding electrocatalytic activity may be ascribed to the synergistic effect between the MoO2 and MoS2 heterostructures.